Dry-land strength and conditioning for prepubertal and peripubertal swimmers - Amaro, Nuno (2018)
Swimming performance depends on the optimal interaction of several factors. Strength is one of those factors, being the ability to apply in-water force determinant in short swimming distances. So, dry-land Strength and Conditioning (S&C) training is usual in swimming prescription where the goal is to enhance performance and/or prevent injuries. However, there is a lack of investigations over this matter, particularly with age group swimmers. Thus, the objective of this article is to provide coaches a practical proposal to enhance swimming performance through the adding of an S&C program to their swimming prescription, in age group swimmers.